Optimalisasi Citra dalam Penghitungan Calsium Scoring dengan Variasi Scan Type dan Slice Thickness (Studi Pendahuluan Dilakukan Dengan Menggunakan Modifikasi Phantom Thorax di RS Telogorejo Semarang) - Bagus Dwi Handoko; Ari Suwondo; Jeffri Ardiyanto (Poltekkes Kemenkes Semarang, 2015)
Background : Examination of Calcium scoring in Radiology Departement Telogorejo Hospital Semarang using CINE scan type and recon phase images using a slice thickness of 2.5mm, this affect will be plaque with small size cann’t to calculate. Aim : The Purpose of this study was to determine the variation of parameters of calcium scoring MSCT scan examination right in calculating optimal plaque.Methods : The study was preceded by Pre experiments using a thorax phantom with an added 3-calcium artificial heart is likened to the RCA, LCX, LAD and have determined the weight and volume. Experiments with 10 patient samples by applying the best parameters from the pre experiment. Statistical analysis of the results of research conducted by Paired T-Test, while the assessment of the quality radiographs evaluated by an expert in this specialist radiology by providing anatomical criteria scores with 3 choices of items (not clear = 1, is quite clear = 2 and obvious = 3)Result : The volume of plaque is embedded in the thorax Panthom 900mm3. Results of pre experiments with hellical scan type and pitch of 0.5, 0.9, 1.3 in a score of plaque volume is 104mm3, 67mm3, 60mm3. While the scan type CINE with slice thickness 0.625mm, 1.25mm, 2.5mm produces a score of volume plaque is 880mm3, 878mm3, 867mm3. Further experiments were performed by applying parameters with the best result is CINE scan with variations slice thickness 0,625mm, 1.25mm, 2.5mm. To determine the best parameters assessment of image quality with the results on slice thickness 0.625mm was 2.2 (quite obvious), slice thickness 1,25mm scoring average of 2.7 (quite obvious), and slice thickness 2.5 mm average scoring 2.9 (obviously). While image noise on the slice thickness 0.625mm, 1.25mm, 2.5mm, namely 2.7(very high), 1.6 (low), 1.1 (low).Conclusions : Selected parameters that calculate optimal scoring calcium and low noise image for MSCT scan calcium scoring in Telogorejo Hospital Semarang is Scan type CINE with slice thickness variation 1,25mm